Resolvin E1, resolvin D1 and resolvin D2 inhibit constriction of rat thoracic aorta and human pulmonary artery induced by the thromboxane mimetic U46619. (26th February 2018) - Jannaway, Melanie; Torrens, Christopher; Warner, Jane A; Sampson, Anthony P
Abstract : Background and Purpose: The ω‐6 fatty acid‐derived lipid mediators such as prostanoids, thromboxane and leukotrienes have well‐established roles in regulating both inflammation and smooth muscle contractility. Resolvins are derived from ω‐3 fatty acids and have important roles in promoting the resolution of inflammation, but their activity on smooth muscle contractility is unknown. We investigated whether resolvin E1 (RvE1), resolvin D1 (RvD1) and resolvin D2 (RvD2) can modulate contractions of isolated segments of rat thoracic aorta (RTA) or human pulmonary artery (HPA) induced by the α1 ‐adrenoceptor agonist phenylephrine or the stable thromboxane A2 mimetic U46619. Experimental Approach: Contractile responses in RTA and HPA were measured using wire myography. Receptor expression was investigated by immunohistochemistry. Key Results: Constriction of RTA segments by U46619, but not by phenylephrine, was significantly inhibited by pretreatment for 1 or 24 h with 10–100 nM RvE1, RvD1 or RvD2. The inhibitory effect of RvE1 was partially blocked by a chemerin receptor antagonist (CCX832). RvE1 at only 1–10 nM also significantly inhibited U46619‐induced constriction of HPA segments, and the chemerin receptor, GPR32 and FPR2/ALX were identified in HPA smooth muscle. Conclusion and Implications: These data suggest that resolvins or their mimetics may prove useful novel therapeutics in diseases such as pulmonary arterial hypertension, which are characterized by increased thromboxane contractile activity.